Geological hazards in the Oujiang estuary in the Zhejiang Province, China: type, distribution, and origin - Jiang, Shenghui; Dong, Chao; Feng, Jing; Cheng, Haiyan; Yang, Jiaojiao; Li, Meina; Wang, Jianqiang; Chen, Xuanbo; Zhou, Yubo (Frontiers in Earth Science, 2023)
As our understanding of the ocean and its uses continues to advance, countries worldwide with ocean access are implementing new marine strategies. For example, understanding marine geological disasters can help develop the use of ocean resources and oceanic engineering. Therefore, this study used recent data from the Oujiang Estuary, a nearshore area in China, to determine its geological hazards. The geological hazards were classified as active or restricted based on topography, geomorphology, shallow seismic profile, single-channel seismic profile, and geological drilling data. Active geological hazards primarily include shallow gas and active sand waves, whereas restrictive geological hazards include irregularly buried bedrock, erosion channels, steep submarine slopes, and buried paleochannels. We also evaluated the distribution characteristics and scope, such as the vertical distribution of shallow gas based on the seismic profiles, drilling rock facies, methane, and carbon dioxide contents in the top air, and the isotope values. We found that shallow gas was vertically distributed among multiple layers. The main gas-bearing layers were the clayey silt and sandy (silt) clay layers of the early Holocene and late Pleistocene strata. The shallow gas content was relatively low in the coarse sediment layer at the bottom of the late Pleistocene succession. Generally, the Holocene and late Pleistocene deposits do not contain gas, and the gas content in the middle and late Pleistocene strata (at greater depths) is relatively low. The combined effects of the regional geological structure, sea level changes, modern hydrodynamics, and human activities have formed the geological environment of the Oujiang Estuary.